Die teologiese wortels en stuktuur van die Heidelbergse Kategismus: "n Oorsig - Schulze, L.F. (Hervormde teologiese studies, 1994)
The theological roots and structure of the Heidelberg Catechism: An overview Some theological roots of the Heidelberg Catechism are considered by taking into account possible viewpoints borrowed from existing Reformed catechisms and prominent sixteenth-century Reformers. Contributions of members of the committee that compiled the Heidelberg Catechism are also pointed out. The structure of the Heidelberg Catechism is etched against the background of the catechisms of Luther and Calvin.